Brush border Myosin Ia has tumor suppressor activity in the intestine - Mazzolini, Rocco (National Academy of Sciences, 2012)
The loss of the epithelial architecture and cell polarity/differentiation is known to be important during the tumorigenic process. Here we demonstrate that the brush border protein Myosin Ia (MYO1A) is important for polarization and differentiation of colon cancer cells and is frequently inactivated in colorectal tumors by genetic and epigenetic mechanisms. MYO1A frame-shift mutations were observed in 32% (37 of 116) of the colorectal tumors with microsatellite instability analyzed, and evidence of promoter methylation was observed in a significant proportion of colon cancer cell lines and primary colorectal tumors. The loss of polarization/differentiation resulting from MYO1A inactivation is associated with higher tumor growth in soft agar and in a xenograft model. In addition, the progression of genetically and carcinogen-initiated intestinal tumors was significantly accelerated in Myo1a knockout mice compared with Myo1a wild-type animals. Moreover, MYO1A tumor expression was found to be an independent prognostic factor for colorectal cancer patients. Patients with low MYO1A tumor protein levels had significantly shorter disease-free and overall survival compared with patients with high tumoral MYO1A (logrank test P = 0.004 and P = 0.009, respectively). The median time-to-disease recurrence in patients with low MYO1A was 1 y, compared with >9 y in the group of patients with high MYO1A. These results identify MYO1A as a unique tumor-suppressor gene in colorectal cancer and demonstrate that the loss of structural brush border proteins involved in cell polarity are important for tumor development.